2022
DOI: 10.1523/eneuro.0140-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A1 Enhances Endothelial Cell Survival in anIn VitroModel of ALS

Abstract: Altered lipoprotein metabolism is considered a pathogenic component of amyotrophic lateral sclerosis (ALS). Apolipoprotein A1 (ApoA1), a major high-density lipoprotein (HDL) protein, is associated with prevention of vascular damage. However, ApoA1’s effects on damaged endothelium in ALS are unknown. This study aimed to determine therapeutic potential of ApoA1 for endothelial cell (EC) repair under a pathologic condition reminiscent of ALS. We performed in vitro studies using mouse brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Notably, Garbuzova-Davis et al [ 89 ] investigated the therapeutic potential of ApoA1 on mBEC status in ALS-like conditions in vitro. The results showed that adding ApoA1 to culture media in a dose-dependent manner protected mBECs from cell injury induced by exposure to plasma from symptomatic G93A SOD1 mice.…”
Section: Noncellular Approach To B-cns-b Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, Garbuzova-Davis et al [ 89 ] investigated the therapeutic potential of ApoA1 on mBEC status in ALS-like conditions in vitro. The results showed that adding ApoA1 to culture media in a dose-dependent manner protected mBECs from cell injury induced by exposure to plasma from symptomatic G93A SOD1 mice.…”
Section: Noncellular Approach To B-cns-b Repairmentioning
confidence: 99%
“…The greatest reduction in cell death was found at ApoA1 concentration of 100 µg/mL. Also, co-culturing mBECs and hBMEPCs in ALS mouse plasma demonstrated that hBMEPCs secreted ApoA1, which integrated into mouse ECs via an activated PI3/Akt signaling pathway to exert beneficial effects [ 89 ]. These initial results suggest that ApoA1 is a promising agent for B-CNS-B repair, but the authors noted that ECs were cultured in fetal bovine serum, which may have influenced the lipid content of ECs.…”
Section: Noncellular Approach To B-cns-b Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural properties of ApoA-I are harnessed in the synthesis of HDL nanotherapeutics as a naturally available blue print for design [ 75 , 76 ]. Apart from offering structural advantages to HDL nanoparticles as a scaffold for stability, HDL-associated ApoA-I is responsible for a majority of anti-inflammatory and atheroprotective properties of HDL, especially in promoting cholesterol efflux and preventing the migration of monocytes to the inflamed endothelia [ 77 , 78 , 79 , 80 , 81 ]. ApoA-I gene transfer in mice reduces TLR4 expression on the endothelial cells, which further regulates the expression of ICAM-1 and VCAM-1, hence controlling leucocyte migration across endothelia in response to inflammation [ 82 ].…”
Section: High-density Lipoproteins Are Self-assembling Nanoparticlesmentioning
confidence: 99%